Mother Nature is trying to kill you : a lively tour through the dark side of the natural world - Riskin, Dan (Simon & Schuster, 2014)
Using the seven deadly sins as a road map, Riskin offers dozens of jaw-dropping examples that illuminate how brutal nature can truly be and shows ways this deadly world has shaped us as humans and what our responsibilities are to this terrible, wonderful planet we call home.